The performance environment of the England youth soccer teams: A quantitative investigation - Pain, M. A.; Harwood, C. G. (Journal of Sports Sciences, 2008)
We examined the performance environment of the England youth soccer teams. Using a conceptually grounded questionnaire developed from the themes identified by Pain and Harwood (2007), 82 players and 23 national coaches and support staff were surveyed directly following international tournaments regarding the factors that positively and negatively influenced performance. The survey enabled data to be captured regarding both the extent and magnitude of the impact of the factors comprising the performance environment. Overall, team and social factors were generally perceived to have the greatest positive impact, with players and staff showing high levels of consensus in their evaluations. Team leadership and strong team cohesion were identified by both groups as having the greatest positive impact. Overall, far fewer variables were perceived to have a negative impact on performance, especially for players. The main negatives common to both groups were players losing composure during games, player boredom, and a lack of available activities in the hotel. The major findings support those of Pain and Harwood (2007) and in using a larger sample helped to corroborate and strengthen the generalizability of the findings.